Tratamiento Contable de la Propiedad, Planta y Equipo de la empresa “LEON DE JUDA SEGURIDAD PRIVADA LEOJUS CIA LTDA” - Cabezas Vargas, Joshua Alberto (2020)
The purpose of this case study is to show the accounting treatment of the property, plant and equipment of the company "LEON DE JUDA SEGURIDAD PRIVADA LEOJUS CIA LTDA, the company is regulated by the Superintendency of Companies, the Internal Revenue Service, Ministry of the Interior, Ministry of Labor. It is understood that a PPE is an asset that the company owns that were acquired by the company through a purchase or the construction of the same, in the case of the building, the correct initial and subsequent measurement of these assets will reasonableness in the financial statements of the company. During the investigation, an interview was carried out with the accounting staff to obtain information on the management of the company's PPE. The essential results obtained from the research is that the institution did not correctly apply the accounting regulations when recognizing the value of the land, due to ignorance of the application Section 17 Properties, Plant and Equipment of the IFRS for SMEs, also in some PPE depreciation was not applied correctly therefore there is no exact valuation of the assets.